Technical and economic evaluation of an engine and irrigation pump using a T-type mixer for natural gas - ElHelew, Waleed Kamel; Abdelmaqsoud, Abdallah Mahmoud; ElBagoury, Khaleed Faran; Shanan, Hayder AbdElHussein (Frontiers in Mechanical Engineering, 2023)
Energy is regarded as one of the most crucial components in the industrial process. Numerous measurements were made in the year 2021 in the workshops of the Agricultural Engineering Department, Faculty of Agriculture, Ain Shams University, Egypt, using a gasoline engine (single cylinder with air-cooling) that was used to power an irrigation pump with a discharge diameter of 2 inches that was manufactured in Egypt. To combine natural gas and air before entering the engine, a variety of mixers were created. Four different types of mixers were employed with iron pipes of various sizes (90 angle T mixer, 45 angle T mixer, 30 angle T mixer, and venture mixer "VM"). 1750, 2300, 2900, and 3500 rpm were the engine shift speeds. The water pump was powered by natural gas and gasoline, respectively. The findings in this study focused on the evaluation of technical indicators for several types of mixers that combine natural gas and air to power an irrigation pump. where the actual power (Braking power) is superior to all types when operating with gasoline was (3.07 kW) A comparison with the use of natural gas, where the mixer type (T45) (2.83 kW) was 7.8% less than gasoline. The lowest Specific fuel consumption (S.fc) for gasoline was (219.025 gm/Kw.h) at an engine speed of (2900 rpm), The lowest (S.fc) for the types of mixers was the mixer (T45) was (234.612 gm/Kw.h) at an engine speed of (2900 rpm) and an increase of 6.6. % over gasoline. The highest pump discharge was with the T45 mixer (528.133 L/min), an increase of 2.1% over gasoline. The highest actual hydraulic power with 45T type mixer compared to other type T mixers (0.6 kw) was 10.5% lower than that of gasoline. As for the economic indicators, the lowest net present value (NPV) at the mixer type (T90) was (77219.5), and the highest (NPV) when carrying the mixer type (T45) was (106900.7). That the lowest benefit-cost ratio (B/C) was the mixer type (VM) was (1.38), and the highest (B/C) when carrying the mixer type (T45) was (1.54).